Sistem Informasi Penilaian Pertandingan Pencak Silat - Faozi Latif; Syahriani Syahriani (UIN Sumatera Utara, 2021)
Abstract — Pencak silat is a traditional martial art sport originating from the archipelago. In addition, pencak silat is a game or skill in self-defense by fending off, attacking or defending oneself using or without weapons. In Indonesia itself, there are many pencak silat organizations, one of which is the West Jakarta branch of PSHT. This pencak silat organization has been established since 1903, but unfortunately, even though it has existed for a long time, every time it holds a match the scoring system still uses the conventional method, namely the value of the match results using paper media. With a scoring system that is still very simple, it is felt to be very ineffective and efficient, because sometimes the note paper is lost, or damaged accidentally, it takes a long time to see reports on the results of matches that have taken place and have opportunities for cheating or unfairness in matches. . Judging from these conditions, we are trying to develop an online pencak silat match assessment information system using a prototype software model and MYSQL database, where this information system can facilitate admins, operators and judges on duty in a match to make it easier and more efficient. improve the effectiveness and efficiency of the match assessment process.